2019
DOI: 10.1111/jcmm.14766
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer cell–derived exosomal microRNA‐27a promotes angiogenesis of human microvascular endothelial cells in pancreatic cancer via BTG2

Abstract: Pancreatic cancer (PC) remains a primary cause of cancer‐related deaths worldwide. Existing literature has highlighted the oncogenic role of microRNA‐27a (miR‐27a) in multiple cancers. Hence, the current study aimed to clarify the potential therapeutic role of PC cell–derived exosomal miR‐27a in human microvascular endothelial cell (HMVEC) angiogenesis in PC. Initially, differentially expressed genes (DEGs) and miRs related to PC were identified by microarray analysis. Microarray analysis provided data predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…Besides, accumulating shreds of evidence proved that exosomes play an essential role in pancreatic cancer angiogenesis [51]. Shang et al reported that PC cellderived exosomal microRNA-27a significantly stimulated the angiogenesis of HMVEC in pancreatic cancer through BTG2 [52]. In conclusion, exosomes affect pancreatic cancer progression by regulating essential features such as angiogenesis, EMT, cell proliferation, and metastasis.…”
Section: Leading Significant Clinically Relevant Roles Of Exosomes Inmentioning
confidence: 97%
“…Besides, accumulating shreds of evidence proved that exosomes play an essential role in pancreatic cancer angiogenesis [51]. Shang et al reported that PC cellderived exosomal microRNA-27a significantly stimulated the angiogenesis of HMVEC in pancreatic cancer through BTG2 [52]. In conclusion, exosomes affect pancreatic cancer progression by regulating essential features such as angiogenesis, EMT, cell proliferation, and metastasis.…”
Section: Leading Significant Clinically Relevant Roles Of Exosomes Inmentioning
confidence: 97%
“…Putative miR-181a-5p binding sites in SNHG12 and binding sites in the 3′-untranslated region (UTR) of NEGR1 to miR-181a-5p were predicted using StarBase ( , v2.0; September 2013 release) and TargetScan ( , v7.2; March 2018 release) ( 26 ). Sequence fragments SHNG12-wild-type (WT) and SHNG12-mutant (MT) and WT and MT 3′-UTR fragments of NEGR1 containing putative miR-181a-5p binding sites were cloned into pmirGLO dual-luciferase reporter vectors (Promega Corporation) and confirmed by sequencing using Illumina MiSeq MiSeqdxDNA (Illumina, Inc.) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that miR-27a is overexpressed in cancer tissues from PaCa patients as well as PaCa cell lines [ 147 ]. PaCa-derived exosomes containing miR-27a can induce proliferation, invasion and angiogenesis in human microvascular endothelial cells (HMVECs) by suppressing B-cell translocation gene 2 (BTG2), which promotes PaCa cell survival and growth [ 121 ]. In contrast, in vivo studies using PaCa animal models have demonstrated miR-339-5p can inhibit cell invasion and migration by down-regulating the expression the zinc finger protein ZNF689.…”
Section: Exosomes and Paca Metastasismentioning
confidence: 99%